2004
DOI: 10.1182/blood-2003-04-1216
|View full text |Cite
|
Sign up to set email alerts
|

Blood plasmacytoid dendritic cell responses to CpG oligodeoxynucleotides are impaired in human newborns

Abstract: Plasmacytoid dendritic cells (pDCs) respond to unmethylated cytosinephosphate-guanosine (CpG) motifs present in bacterial DNA or unmethylated synthetic oligodeoxynucleotides (CpG). In order to assess the function of pDCs in human newborns, interferon-␣ (IFN-␣) production induced by CpG 2216 and phenotypic maturation of pDCs in response to CpG 2006 were compared in cord blood and adult blood. We first observed that neonatal pDCs displayed decreased up-regulation of CD80, CD83, CD86, and CD40, whereas HLA-DR and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
85
4
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 155 publications
(102 citation statements)
references
References 18 publications
(21 reference statements)
10
85
4
3
Order By: Relevance
“…In a previous work, we observed an impaired IFN-a production in enriched cord blood pDC following a TLR9 stimulation using CpG oligonucleotides [8]. Herein, we first confirmed that highly purified cord blood pDC were impaired in their capacity to mount significant IFN-a response whatever the dose of CpG A used for their stimulation (Supporting Information Fig.…”
Section: Ifn-a/b Induction Through Tlr7 Is Impaired In Cord Blood Pdcsupporting
confidence: 64%
See 1 more Smart Citation
“…In a previous work, we observed an impaired IFN-a production in enriched cord blood pDC following a TLR9 stimulation using CpG oligonucleotides [8]. Herein, we first confirmed that highly purified cord blood pDC were impaired in their capacity to mount significant IFN-a response whatever the dose of CpG A used for their stimulation (Supporting Information Fig.…”
Section: Ifn-a/b Induction Through Tlr7 Is Impaired In Cord Blood Pdcsupporting
confidence: 64%
“…This pathway has been shown to be dependent on NF-jB activation [6,7]. Although pDC are present in significant numbers in human cord blood, there is evidence that they do not function as their adult counterparts since we found that they secrete less IFN-a upon exposure to CpG [8].…”
Section: Introductionmentioning
confidence: 48%
“…30 However, plasmacytoid dendritic cells from human cord blood produced much less IFN-a in response to CpG oligonucleotides than cells from adult blood. 31 Although spontaneous in vitro proliferation of fetal and neonatal T lymphocytes was found to be greater than that of adults, they responded poorly when simulated with phytohaemagglutinin or allogeneic stimulator cells; IL-2, IL-4 and IFN-g secretion was only modest in neonatal T cells and entirely absent in those from fetuses. 32 The consequences of this immune hypo-responsiveness were observed when a marker gene was delivered by an adenovirus vector to the airways of neonatal and adult cotton rats.…”
Section: Adaptive Immunitymentioning
confidence: 95%
“…In the majority of studies, the function of neonatal DCs has been shown to be defective compared to adult DC function (3,6). Increasing evidence suggests that neonates of HBV carrier mothers are exposed to virions and/or viral antigens in utero even if they do not acquire the infection (17,18,23,30).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of DCs has been demonstrated by experiments showing that neonatal T cells can reach adult-like responses when stimulated with isolated allogeneic adult DCs (2). The main dysfunctions of neonatal DCs include low circulating numbers, low levels of costimulatory-molecule expression, decreased induction of cytokine production, and decreased capacity to stimulate naïve T cells (3,12,28).…”
mentioning
confidence: 99%